2020
DOI: 10.1126/science.aba4357
|View full text |Cite
|
Sign up to set email alerts
|

An intrinsic oscillator drives the blood stage cycle of the malaria parasite Plasmodium falciparum

Abstract: The blood stage of the infection of the malaria parasite Plasmodium falciparum exhibits a 48-hour developmental cycle that culminates in the synchronous release of parasites from red blood cells, which triggers 48-hour fever cycles in the host. This cycle could be driven extrinsically by host circadian processes or by a parasite-intrinsic oscillator. To distinguish between these hypotheses, we examine the P. falciparum cycle in an in vitro culture system and show that the parasite has molecular signatures asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
86
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(100 citation statements)
references
References 55 publications
7
86
0
Order By: Relevance
“…This range is insufficient to explain most of the variation in multiplication rates, and no significant correlation was shown here, but it could plausibly contribute a minor component of the variation and deserves future attention although other phases of the cycle may have a greater effect. The typical multiplication cycle length is considered to be 48 h, and this period was used as the nominal generation time for the standardised analysis of multiplication here, but actual duration of multiplication cycles have been shown to vary among several cultured clones by up to 1.5 fold 27 , 28 , so it would be interesting to investigate this parameter in clinical isolates. It is also possible that transcriptome analyses might identify genes that regulate mechanistic differences.…”
Section: Discussionmentioning
confidence: 99%
“…This range is insufficient to explain most of the variation in multiplication rates, and no significant correlation was shown here, but it could plausibly contribute a minor component of the variation and deserves future attention although other phases of the cycle may have a greater effect. The typical multiplication cycle length is considered to be 48 h, and this period was used as the nominal generation time for the standardised analysis of multiplication here, but actual duration of multiplication cycles have been shown to vary among several cultured clones by up to 1.5 fold 27 , 28 , so it would be interesting to investigate this parameter in clinical isolates. It is also possible that transcriptome analyses might identify genes that regulate mechanistic differences.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, daily oxidation-reduction rhythms exist within mammalian RBCs independent of a TTFL clock [45], are evolutionarily conserved [46] and may be linked to cellular flux in magnesium ions [47]. Recent work suggests that these rhythms are unlikely to impact on development during the IDC [9,24], but this is yet to be formally tested.…”
Section: Discussionmentioning
confidence: 99%
“…Determining how many cycles it will take a population of parasites to fully desynchronize is complex because the rate will be obscured by changes in density [ 33 ]. Thus, without sophisticated modelling that accounts for infection dynamics, it is difficult to determine whether desynchronization of the IDC, when hosts are in constant conditions, is due to a free-running oscillator belonging to the parasite [ 9 ]. Second, even in completely asynchronous infections, the expansion of parasite number due to each asexual stage replacing itself with multiple progeny can generate the illusion of strong synchrony [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Aiming to investigate the rhythmic gene expression in parasites in absence of host cues, Smith et al 41 analyzed the gene expression from four different strains of P. falciparum. The authors showed that P. falciparum presents rhythmic gene expression, pointing out an intrinsic oscillator in the parasite.…”
Section: Discussionmentioning
confidence: 99%